Is There a Bulldozer in your Model?. Issue 3 (5th March 2019) - Lazarus, Eli D.; Goldstein, Evan B.
Abstract: Deliberate, real‐time human interventions into geomorphic processes are a phenomenon that no off‐the‐shelf numerical model of morphodynamics is built to capture. We suggest that active, responsive human processes that affect sediment transport during major storm events be included in evolving efforts to model geomorphic change. Key Points: Humans make deliberate, real‐time interventions into geomorphic processes, especially during major storm events Existing morphodynamic models are not built to account for active, responsive human interventions Evolving model platforms may need to explicitly address active human interventions as morphodynamic processes unto themselves